Уг поты жадеме: [кылбуръёс, поэмаос, берыктэмъёс] / Семен Карпов - Карпов Семен Карпович (Удмуртия, 2016)
Экземпляры: 6 (20240216) / Инвентарный номер: 56620 / Цена: 100.00 / Авт.знак: К 26 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6